‘I Would Prefer Not To’ - On the Virtues of Abjection in Contemporary European Cinema and Society - Jeremi Szaniawski (Etkileşim, 2022)
Shortly before his sudden and untimely passing, film scholar Thomas Elsaesser focused his attention on the concept of abjection, noting a pronounced shift away from liberal democracy in Western Europe, and calling for a new paradigm but also new attitudes to address increasingly invasive and controlling societal models. In the two years since, one of the most important contemporary thinkers on matters of states of exception, Giorgio Agamben, has also pointed to these new developments, and made very pronounced attempts in civil society to alert his fellow citizens to these developments and what he perceives as their disquieting implications. In this article, I take stock with the legacy of Elsaesser and with Agamben’s recent remarks, and look at a film which eminently fits in a corpus of films dealing with abjection and states of exception, Border (2018). Through it, I reflect on the fates of the millions of Europeans who, in recent months, and for various reasons, have decided to refuse changes to the way civil society’s freedom and functioning have been conceived hitherto -even as their progressive erosion has been undeniable at least over the course of the last twenty years or so. In so doing, these people who refuse the newly decreed (and ever modulating) social norms and prescriptions have literally entered a process of (self) abjectifying, which in many cases may have been latent to begin with. Ultimately, the fate of the two protagonists of Border suggests two of the various ways in which these new ‘abjects’ can continue to live and operate in society or relegate themselves to its fringe -all the while remaining fully sentient and emoting beings worthy of our compassion and consideration.